(untitled) (Baghdad Science Journal, 2011)
The phenyl hydrazine was react readily with acetic acid chloride in [1:2] ratio in alkyl of ethanolic solution, and refluxe for five hours to produce a new ligand of (N-Carboxymethyl-N-phenyl-hydrazino)-acetic acid [H2L].